2018
DOI: 10.5194/piahs-379-409-2018
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for rainwater harvesting system design and assessment for the city of Johannesburg, South Africa

Abstract: Abstract. As water demand increases rainwater harvesting (RWH) systems are increasingly being installed for water supply but comprehensive hydrologic design guidelines for RWH do not exist in many parts of the world. The objective of this study was to develop guidelines for the hydrologic design and assessment of rainwater harvesting (RWH) systems in the City of Johannesburg, South Africa. The data for developing the guidelines were mainly obtained from multiple daily simulations of potential RWH systems in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Comparing the present study with another similar study, it was observed that a 4,000 L concrete tank installed with a roof area of 40 m 2 was adequate to take care of the water demands of a household consisting of four members [34,35]. Similarly, a study conducted by Woltersdorf et al in [36,37]. According to Imteaz et al, a tank size of 7,000 L is required to achieve 100% reliability for toilet flushing and laundry [38].…”
Section: Mass Curve To Derive the Storage Tank Capacitysupporting
confidence: 67%
“…Comparing the present study with another similar study, it was observed that a 4,000 L concrete tank installed with a roof area of 40 m 2 was adequate to take care of the water demands of a household consisting of four members [34,35]. Similarly, a study conducted by Woltersdorf et al in [36,37]. According to Imteaz et al, a tank size of 7,000 L is required to achieve 100% reliability for toilet flushing and laundry [38].…”
Section: Mass Curve To Derive the Storage Tank Capacitysupporting
confidence: 67%
“…The average functionality status of the RWH schemes is 22.94% which is below the average functionality standard of RWH, which is 50% [NDIRITU et al 2018]. As per the result of the study shown in Figure 6 most of the schemes are non-functional.…”
Section: Roof Water Harvestingsmentioning
confidence: 75%